Detection of jamming attack at Kolej Komuniti Masjid Tanah - Haron, Haliza (2015)
Wireless network grows very fast; the flawed security of most of those networks becomes more apparent. People are extremely adopting to use wireless network to access Internet. The last ten years have seen an explosion in the use of wireless technology. The wireless network medium has become target to the attackers. This study will focus on jamming attack and the case study has been done at Kolej Komuniti Masjid Tanah (KKMT). This study will involve two important phases which are investigation and implementation phase. The investigation phase is the process of getting information from previous research to get an overview about the scope of the study. The simulation of the wireless network using Opnet Modeler has been done during implementation phase. The simulation is to get the result of the affected parameters that have been choosing in investigation phase. The results generated from the simulation process has analyze four parameters affected and can be used to detect jamming attack at KKMT are network load, delay, throughput and error rate.